Inserção da competência em informação em documentos prescritivos e normativos e a prática de professores do ensino fundamental da rede municipal da educação – ciclo I, na cidade de Marília-SP - Coneglian, André Luís Onório [UNESP] (2013)
Analyzes the inclusion of Information Literacy theme in international, national and local documents related to education. We also sought to ascertain how this theme is present in everyday school life. The argument is that although the Information Literacy is addressed in official documents of national and international scope, it is not present in the school routine. It is understood that the development of the Information Literacy is an educational process, which should be started in a conscious and planned in the educational field, as an integral part of the school curriculum. The overall goal of the research was to analyze the Information Literacy insertion in the early grades of elementary school in the municipal education of Marilia City, São Paulo, Brazil through official documents and a case study with a group of elementary school teachers - cycle I. We used a triangulation approach. Official documents of Education and Librarianship/Information Science institutions from international, national and local levels were analyzed. There was a basic course in Information Literacy for a group of 20 teachers from the first cycle of basic education Marilia City to investigate the relationship between the subject and the school routine. The records produced during the course were collected. The libraries of 10 schools to which they belong course participants were characterized. The analysis was done through the categorization: thematization, standardization and implementation of Information Literacy. The results indicate that the Information Literacy is thematized and standardized documents in Information Science and Education, including the National Curriculum. However, teachers in the case study demonstrated not know the themes and practices related to Information Literacy, showing a deficient formation and decontextualized reality of the... (Complete abstract click electronic access below)